PET-CT staging of the neck in cancers of the oropharynx: patterns of regional and retropharyngeal nodal metastasis - Tauzin Marcie; Rabalais Amy; Hagan Joseph L; Wood Charles G; Ferris Robert L; Walvekar Rohan R (World Journal of Surgical Oncology, 2010)
Abstract Objective To study the retropharyngeal lymph node status (RPLN) by pretreatment PET-CT imaging in patients with squamous cell carcinomas of the oropharynx (OPSCC). Study Design: Retrospective. Methods 101 patients with a biopsy proven OPSCC were identified. 53 patients meeting inclusion criteria were further analyzed. Results The frequency of RPLN was 20.8% (11/53). Advanced T stage cancer (OR = 5.6250, 95% CI: 1.06 - 29.80, p = 0.0410) and advanced clinical N stage cancer (i.e. N2+) had higher odds (OR = 3.9773, 95% CI: 0.9628 - 16.4291) of being RPLN positive as compared to N0-1 patients. Conclusions Pre-treatment PET-CT can be used as a staging tool to aid in treatment planning of OPSCC, as rates of RPLN and nodal metastasis are consistent with those reported in the literature. Advanced T and N stage are associated with a greater odds ratio of being RPLN positive by PET-CT imaging.